Effect of coconut water concentration and the duration of true shallot seed soaking on growth and production of shallot (Allium ascalonicum L.) of Tuk-Tuk varieties - Beatrix Sofranes Napitupulu; Ratna Rosanty Lahay; Asil Barus (Universitas Sumatera Utara, 2018)
This research was conducted to find out the effect of coconut water concentration and the duration of true shallot seed soaking on the growth and production of shallot. This research was conducted on community farm at Jalan Bunga Rampai II Gang Saudara, Kelurahan Simalingkar B, Kecamatan Medan Tuntungan, Medan, began from April to August 2017. The research used a Factorial Randomized Block Design with 2 treatment factors: coconut water concentration at 5 levels: 0; 25; 50; 75; 100 %, and duration of seed soaking at 3 levels: 60; 120; 180 minutes. The parameters observed were number of plant height at 2 to 7 weeks after transplanting (WAT), bulb diameter, and dry bulb weight. The result of this research showed that coconut water concentration had no significant effect on all observation parameter. The duration of seed soaking treatment had significant effect on plant height and dry bulb weight. The highest dry bulb weight was obtained at 120 minutes of seed soaking. The interaction of coconut water concentration and the duration of true shallot seed soaking treatment had no significant effect on all observation parameters.Keywords: coconut water concentration, duration of seed soaking, true shallot seed